Model to assess the factors of 10-year future risk of coronary heart disease among people of Framingham, Massachusetts - Azizur Rahman; Arifa Tabassum (Intelektual Pustaka Media Utama, 2020)
In earlier decade, heart disease was the most common cause of death in the US. Among the many important risk factors such as age, number of cigarettes smoke could help in determining the odds of having corona heart disease (CHD) when modeling with other important factors. We analyzed ongoing cardiovascular study on residents of the town of Framingham, Massachusetts, US to predict the 10-year risk of future CHD. We applied the Binary logistic regression model to assess the strength of the association of factors (such as gender, age, number of cigarettes smoke, total cholesterol level) in predicting the odds of having CHD in study population. Results showed that gender, age, number of cigarette smoke, systolic blood pressure were statistically significant and the increased age and cigarettes per day increase the odds of having 10-year risk of CHD. However, the noticeable finding was that patients with Diabetes at higher glucose level have the higher odds of having 10-year risk of CHD than with low level of glucose concentration among the residents of Framingham study.